Essentials of interpretative phenomenological analysis - Smith, Jonathan A.; Nizza, Isabella E. (Essentials of qualitative methods series, 2022)
"The brief, practical texts in the Essentials of Qualitative Methods series introduce social science and psychology researchers to key approaches to to qualitative methods, offering exciting opportunities to gather in-depth qualitative data and to develop rich and useful findings. Essentials of Interpretative Phenomenological Analysis is a step-by-step guide to a research method that investigates how people make sense of their lived experience in the context of their personal and social worlds. It is especially well-suited to exploring experiences perceived as highly significant, such as major life and relationship changes, health challenges, and other emotion-laden events. IPA studies highlight convergence and divergence across participants, showing both the experiential themes that the participants share and the unique way each theme is manifested for the individual. About the Essentials of Qualitative Methods book series: Even for experienced researchers, selecting and correctly applying the right method can be challenging. In this groundbreaking series, leading experts in qualitative methods provide clear, crisp, and comprehensive descriptions of their approach, including its methodological integrity, and its benefits and limitations. Each book includes numerous examples to enable readers to quickly and thoroughly grasp how to leverage these valuable methods"--